NUTRITIONAL AND MICROBIOLOGICAL PROFILE OF FERMENTED SKIPJACK TUNA VISCERA SILAGE BASED ON MOLASSES VARIATIONS AS A CANDIDATE FOR VALUE-ADDED FEED INGREDIENTS - Yudana, IGP Gede Rumayasa; Hariyoto, Fitroh Fitroh Dwi; Ondang, Hetty MAGRITTHA PAULINE; TUMANDUK, Nova MAGDALENA; WEWENGKANG, Itje ANTI; Ticoalu, Fidel JAMES BONIFACIO; akbar, mohamad; Wowiling, Fernando; Rakhmayeni, Dyah ayu; NATALIA, DESSY ATIKA; Abdillah, Amelia (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
This study aims to evaluate the nutritional and microbiological profiles of fermented skipjack tuna (Katsuwonus pelamis) entrails silage based on variations in molasses addition as a candidate for value-added feed ingredients. The study was conducted from September to November 2025 at the Processing Workshop of the Bitung Marine and Fisheries Polytechnic. The skipjack tuna entrails raw material was fermented for 14 days using probiotics as a source of Lactic Acid Bacteria (LAB) with molasses added at levels of 10%, 20%, and 30%. The parameters tested included crude protein, crude fat, Total Plate Count (TPC), total LAB, and the presence of Salmonella. The results showed that increasing the molasses level tended to decrease the protein content and produced variations in crude fat values in the silage product. Microbiological activity showed that LAB was higher in the 30% molasses treatment, while TPC was relatively stable in all treatments. All samples were declared safe for because they were Salmonella-negative. Overall, fermented skipjack tuna entrails silage with a molasses level of 10% provided a more optimal nutritional and microbiological profile than other treatments, making it a potential candidate for value-added feed ingredients in supporting the sustainable utilization of fishery waste